Site types revisited: Comparison of traditional Russian and Finnish classification systems for European boreal forests. Issue 1 (12th September 2020) - Pohjanmies, Tähti; Genikova, Nadezhda; Hotanen, Juha‐Pekka; Ilvesniemi, Hannu; Kryshen, Alexander; Moshnikov, Sergey; Oksanen, Jari; Salemaa, Maija; Tikhonova, Elena; Tonteri, Tiina; Merilä, Päivi
Abstract: Questions: Forest classifications are tools used in research, monitoring, and management. In Finland, the Cajanderian forest site type classification is based on the composition of understorey vegetation with the assumption that it reflects in a predictable way the site's productive value. In Russia, the Sukachevian forest classification is similarly based on understorey vegetation but also accounts for tree species, soil wetness, and paludification. Here we ask whether Cajander's and Sukachev's forest types are effectively the same in terms of species composition, site productivity, and biodiversity. Location: Boreal forests on mineral soils in Finland and the Russian part of Fennoscandia. Methods: We use vegetation and soil survey data to compare the Cajanderian and the Sukachevian systems in terms of the understorey community composition (that is supposed to define them), soil fertility and tree productivity (that they are expected to indicate), and biodiversity (that is of interest for conservation purposes). We create and employ class prediction models to divide Russian and Finnish sites into Cajander's and Sukachev's types, respectively, based on vegetation composition. We perform cross‐comparisons between the two systems by non‐metric multidimensional scaling ordination and statistical tests. Results: Within both systems, the site types formed similar, meaningful gradients in terms of the studied variables. Certain site types from the two systems were largely overlapping in community composition and arranged similarly along the fertility gradient and may thus be considered comparable. Conclusions: The Cajanderian and the Sukachevian systems were both developed in the European boreal zone but differ in terms of the exact rules by which site types are determined. Our results show that analogous types between the systems can be identified. These findings aid in endeavours of technology and information transfer between Finnish and Russian forests for the purposes of basic or applied ecological research and forest management. Abstract : We examined two traditional, vegetation‐based classification systems of European boreal forests—Cajander's in Finland and Sukachev's in Russia—for their correspondence in terms of community composition and site characteristics. We found similarities between Cajander's and Sukachev's site types, suggesting that at least at a general level they can potentially be used interchangeably in forest research or technology transfer.